Ocular Fundus Changes in Pregnancy Induced Hypertension (Journal of Dhaka Medical College, 2020)
Purpose: Preeclampsia and eclampsia is one of the leading causes of maternal and fetal morbidity and mortality worldwide. Visual disturbances in (pre)eclampsia seem to be frequent phenomena. Therefore, the obstetrician/gynecologist may encounter women with serious, and sometimes debilitating, pathology of the visual pathways.Methods: This is a cross sectional observational study was conducted over a period of 12 months (January 2016-December 2016) at Dhaka Medical College Hospital, Dhaka, Bangladesh. Patients with severe preeclampsia and eclampsia were included in the study. The association was measured with Chi-squared test and p value of 0.05 was treated as significant.Results: During this 12-month period, 100 patients with severe preeclampsia and eclampsia were studied the mean age was 26.4 ± 5.5 years. The association between retinal changes and different variables was statistically significant positive association between the presence of retinal changes and blood pressure (P= 0.0118), proteinuria (P= 0.0025). However, age (P= 0.7123), and gravida (P= 0.7998) were not associated with occurrence of retinopathy in our study. The most common retinal change was noted and narrowing of arterioles, (83%) that retinal changes were significantly more in patients with severe hypertension, exudate (12%) and haemorrhages (10%) observed in present study. The presence of macular edema (5%) and retinal detachment (2%) are the warning signs for termination of pregnancy to save the vision of the mother.Conclusion: It is called that eye is the gateway of medicine, so in pregnancy induced hypertension presence of changes in the retinal arterioles and retinal haemorrhages may indicate similar changes in the placenta. Since the well-being of the foetus depends on the placental circulation, ophthalmoscopic examination of mother’s fundus may give a clue to similar micro-circulation changes in the placenta and indirectly to the foetal wellbeing.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 94-99